SOME CONSEQUENCES OF A SYMMETRY IN STRONG DISTRIBUTIONS - Ranga, A. S.; Deandrade, EXL; Mccabe, J. H. (Academic Press Inc. Jnl-comp Subscriptions, 1995)
Some polynomials and interpolatory quadrature rules associated with strong Stieltjes distributions are considered, especially when the distributions satisfy a Certain symmetric property. (C) 1995 Academic Press, Inc.